2020
DOI: 10.1016/j.ecns.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Practice in Simulation: Evaluation of Repetitive Code Training on Nursing Students’ BLS Team Skills

Abstract: Background: Basic life support (BLS) skills decline rapidly without frequent practice. Deliberate practice (DP) and simulation scenarios have been shown to increase BLS skill retention for nursing students. In addition, BLS implementation in the hospital setting requires effective team skills, which are infrequently addressed in resuscitation courses or in nursing students' practice. An exploratory study to determine the impact of recurrent simulations with DP on BLS team skills was designed for senior nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
(14 reference statements)
0
13
0
10
Order By: Relevance
“…21 For the presentation of results, selected studies were numbered and identified as S1 to S9. [22][23][24][25][26][27][28][29][30] The nine studies included in this review's sample were published between 2011 and 2021. Most of the studies found belong to the EMBASE database, with a total of 5 studies (S4-S8), [25][26][27][28][29] followed by 3 studies from the Web of Science database (S1-S3), [22][23][24] and the ninth study (S9) 30 was found in both databases.…”
Section: Resultsmentioning
confidence: 99%
“…21 For the presentation of results, selected studies were numbered and identified as S1 to S9. [22][23][24][25][26][27][28][29][30] The nine studies included in this review's sample were published between 2011 and 2021. Most of the studies found belong to the EMBASE database, with a total of 5 studies (S4-S8), [25][26][27][28][29] followed by 3 studies from the Web of Science database (S1-S3), [22][23][24] and the ninth study (S9) 30 was found in both databases.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, this type of BLS clinical simulation course was used in our investigation because there is scientific evidence that confirms that students who use BLS simulations, high-fidelity manikins, and other devices that provide corrective feedback during their CPR training have improved compression rates and improved CPR skills compared to those who do not use such devices [ 15 , 23 ]. Another study indicated that frequent practice is needed to maintain CPR skills [ 28 ]. There are several recent investigations that coincide with our results, affirming that clinical simulation is an essential component in nursing education [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that frequent practice is needed to maintain CPR skills [ 28 ]. There are several recent investigations that coincide with our results, affirming that clinical simulation is an essential component in nursing education [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Council of State Boards of Nursing (NCSBN) defines clinical simulation as “an operation or experience that replicates clinical procedure [by] utilizing scenes, high‐fidelity manikins, medium‐fidelity manikins, standardized patients, role acting, skills stations, and computer‐based strategic thinking simulations.” 1 Clinical nursing education has been impacted by profound changes in clinical placements, patient health challenges, and students' direct experiences with health treatment and opportunities to handle problem‐based clinical conditions, as it seeks to help students improve their problem‐solving abilities by integrating academic knowledge from books with the expertize of real‐life scenarios 2 . Therefore, the valuable alternative that has shown to enhance these skills is simulation 3–5 . Simulation is utilized in a range of settings, including clinical education, medical treatment in clinics, and improving the competencies of staff nurses 6 .…”
Section: Introductionmentioning
confidence: 99%